Spinal Cord Injury Research in Mice: 2008 Review - Inge Steuer; Pierre A. Guertin (The Scientific World Journal)
Spinal cord injury (SCI) is an irreversible condition causing damage to myelinated fiber tracts that carry sensation and motor signals to and from the brain. SCI is also associated with gray matter damage and often life-threatening secondary complications. This mini-review aims to provide the nonspecialist reader with a comprehensive description of recent advances made in 2008 using murine models of SCI. A variety of approaches, including advanced genetics and molecular techniques, have allowed a number of key findings in the field of secondary degeneration, repair, regeneration (including insights from peripheral nerve lesion models), metabolic dysfunctions, and pharmacological neuromodulation.